Per- and polyfluoroalkyl substances (PFASs) in airborne particulate matter (PM2.0) emitted during floor waxing: A pilot study. (1st January 2022) - Zhou, Jiaqi; Baumann, Karsten; Chang, Naomi; Morrison, Glenn; Bodnar, Wanda; Zhang, Zhenfa; Atkin, Joanna M.; Surratt, Jason D.; Turpin, Barbara J.
Abstract: Per- and polyfluoroalkyl substances (PFASs), with their water- and heat-resistant properties, have been widely used in industrial and consumer products, including floor waxes. Adverse health effects are associated with PFAS exposures (e.g., increased risk of cancer and immunotoxicity); however, exposures resulting from the use of PFAS-containing products are poorly understood. This study examines PFAS emissions during professional floor stripping/waxing and their potential for occupational exposures. We measured PFASs in dust and airborne particulate matter (PM2.0, aerodynamic diameter ≤2.0 μm) before, during, and after floor stripping/waxing activities in three rooms in a university building. PM2.0 samples were analyzed for 34 targeted PFASs by ultra-high performance liquid chromatography coupled to electrospray ionization triple quadrupole mass spectrometer (UHPLC/ESI-MS/MS). In total, ten PFASs were detected in PM2.0 collected during floor stripping/waxing. Five were consistently higher during floor stripping/waxing compared to before (two with 95% confidence interval): perfluoro-2-methoxyacetic acid, perfluorobutanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, and perfluorooctane sulfonic acid. For these five, estimated exposures during floor stripping were 80.6, 320.5, 83.8, 29.6, and 157.7 pg m −3 per hour of floor stripping, respectively, one order of magnitude greater than typical residential indoor and two orders of magnitude greater than ambient outdoor concentrations. Estimated emission rates were 3.0, 9.6, 3.4, 1.5, and 6.5 ng h −1 m −2, respectively (34.6% uncertainty). Inhalation occupational exposures were in the range of 9.42–23.2 pg per kg body weight per hour of floor stripping across the five PFASs. Graphical abstract: Image 1 Highlights: PFASs in dust and airborne particulate matter (PM2.0 ) during professional floor stripping/waxing were measured. PFASs emission rates from floor stripping/waxing were estimated. Significantly higher levels of PFASs were measured during floor waxing. Floor waxing could be an important source of PFAS contamination. Floor waxing workers could have increased occupational health risks due to PFAS exposures.